2001
DOI: 10.1046/j.1439-0280.2001.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

A modified, four‐armed olfactometer for determining olfactory reactions of beneficial arthropods

Abstract: Methods using the reactions of beneficial arthropods to stimuli of prey and habitats are becoming more and more important in the biological control of pests. Especially olfactory cues, which are measurable with so called`olfactometers' are of great importance. In the present study, a modified four-armed airflow olfactometer is described by explaining these modifications. As an example, the results obtained for the predatory ladybeetle Coccinella septempunctata are explained in detail. Various odour sources cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The perennial weeds A. vulgaris, T. vulgare and U. dioica , which showed an increased attraction effect on the adults of different polyphagous predators in ­laboratory tests ( Kranz and Sengonca , 2000; Kranz and Sengonca , unpubl.) with a 4‐armed olfactometer ( Sengonca and Kranz , 2001), had also caused a population increase in these beneficials in lettuce fields and reduced the infestation with aphids. This confirms earlier observations, in which a population increase in beneficials on these attractive plants was described ( Budenberg and Powell , 1992; Kranz and Sengonca , 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perennial weeds A. vulgaris, T. vulgare and U. dioica , which showed an increased attraction effect on the adults of different polyphagous predators in ­laboratory tests ( Kranz and Sengonca , 2000; Kranz and Sengonca , unpubl.) with a 4‐armed olfactometer ( Sengonca and Kranz , 2001), had also caused a population increase in these beneficials in lettuce fields and reduced the infestation with aphids. This confirms earlier observations, in which a population increase in beneficials on these attractive plants was described ( Budenberg and Powell , 1992; Kranz and Sengonca , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great importance of such investigations, there is a lack of research work on the olfactory attractiveness of weeds to polyphagous predators in the field. Recent experiments with a modified olfactometer, conducted in the laboratory ( Sengonca and Kranz , 2001; Kranz and Sengonca , unpubl.) showed that the perennial weed species wormwood Artemisia vulgaris L., tansy Tanacetum vulgare L. and stinging nettle Urtica dioica L. attract some polyphagous predators such as Coccinella septempunctata L., Adalia bipunctata (L.) and Propylea quatuordecimpunctata (L.) (Coleoptera, Coccinellidae) as well as Chrysoperla carnea (Steph.)…”
Section: Introductionmentioning
confidence: 99%
“…to herbivore-attacked plants have been reported recently (Lentz et al 2004;Sengonca and Kranz 2001;Takahashi et al 2001), such information is lacking for S. gilvifrons. In addition, the production of herbivore-induced volatiles differs among plant species and cultivars (Takabayashi et al 1994;Takabayashi and Dicke 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a Y‐shaped ¼‐inch‐diameter glass tube was connected to a Teflon hose; the airflow was adjusted by a vacuum pump and an air delivery system with six charcoal filters (ARS, Gainesville, FL, USA). The air speed was controlled by pressure regulators to provide a constant flow of 100 ml s −1 , as recommended by Sengonca & Kranz (). At the ends of both entrances, the airflow passed through two compartments (Figure ).…”
Section: Methodsmentioning
confidence: 99%